Destination Attributes – Its Role on Constructing Image of Bandung as A MICE Destination in Indonesia - M. Liga Suryadana (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
The MICE business continuously grow. Therefore, the MICE organizer provides an assessment of the city’s destination attributes. The purpose of this study is to disclose the forming factors of the destination. This study uses multiple regression analysis methods with a sample of 150 respondents. Two destination attributes as affordability and activities do not significantly influence the image formation of Bandung as a MICE destination. The simultaneous effect is 88.4%, while the other un-observed factors influence 11.6%. Thus, the availability of complete and high-quality destination attributes in Bandung will improve the city’s image as a MICE destination. Furthermore, it enables Bandung to compete with the other MICE destinations in Indonesia.